Impact of Premenstrual Syndrome (PMS) on Quality of Life among adolescent girls of rural area of Gautam Buddh Nagar: A Cross sectional study - Chauhan, Ambren; Juneja, Khushboo; Tyagi, Neha; Agarwal, Vanshika (Indian Journal of Community Health, 2024)
Background: PMS causes purposeful impairment in efficiency at school/work, impaired relations with friends, , poor social life activities and home responsibilities affecting quality of life. Aims &Objectives: This study was conducted to estimate the prevalence and symptoms of premenstrual syndrome in adolescent girls and to assess the impact of premenstrual syndrome on their quality of life. Methodology: A cross?sectional study was done among 380 adolescent girls using a pretested semi-structured questionnaire residing in rural field study areas of Department of Community Medicine of a medical college. Results: The prevalence of PMS was reported to be 65.7 % . Head ache (66%) was the most frequent symptom followed by acne (60%) and generalized body ache (57%). Only 37.8% of the girls take their quality of life to be good followed by 1.8% as very good when they were asked about experiencing any negative feelings prior to menses like blue mood, despair ,anxiety etc .Around one fourth (26%) of them reported that they never experience any kind of negative feeling .Conclusion: The adolescent girls are in greatest need for physical , psychological support as they experience the most severe PMS symptoms.